2014
DOI: 10.1371/journal.pone.0111872
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling in Cattle Experimentally Infected with Mycobacterium avium subsp. paratuberculosis

Abstract: The sensitivity of current diagnostics for Johne's disease, a slow, progressing enteritis in ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP), is too low to reliably detect all infected animals in the subclinical stage. The objective was to identify individual metabolites or metabolite profiles that could be used as biomarkers of early MAP infection in ruminants. In a monthly follow-up for 17 months, calves infected at 2 weeks of age were compared with aged-matched controls. Sera from all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
63
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 53 publications
12
63
3
Order By: Relevance
“…33 As is well known, acetoacetate is produced 46 In our study, the observed increases in acetoacetate and acetone may be related to the upregulation of fatty acid oxidation in the model rats. 33 As is well known, acetoacetate is produced 46 In our study, the observed increases in acetoacetate and acetone may be related to the upregulation of fatty acid oxidation in the model rats.…”
Section: Discussionsupporting
confidence: 62%
“…33 As is well known, acetoacetate is produced 46 In our study, the observed increases in acetoacetate and acetone may be related to the upregulation of fatty acid oxidation in the model rats. 33 As is well known, acetoacetate is produced 46 In our study, the observed increases in acetoacetate and acetone may be related to the upregulation of fatty acid oxidation in the model rats.…”
Section: Discussionsupporting
confidence: 62%
“…The metabolomic study was quicker and more sensitive at distinguishing infected from noninfected animals. The discrimination was significant regardless of infectious burden and time after infection (at 3, 6, 9, and 12 mo) (53). Although the potential is present, more work needs to be done to accurately predict the progression from latent to active mycobacterial disease, relapse after Definition of abbreviations: DI-MS/MS = direct infusion tandem mass spectroscopy; GC-MS = gas chromatography-mass spectrometry; LC-MS = liquid chromatography-mass spectroscopy; NMR = nuclear magnetic resonance.…”
Section: Metabolomics and Diagnostic Biomarkersmentioning
confidence: 89%
“…Development of biomarkers to identify subclinical MAP-infected cattle, separately or in combination with vaccine use, might prevent further progression of contaminated food products into human and animal food chains [115]. Lessons for effective strategies in controlling Johne’s disease might be learned from comparing the diverse approaches of private organizations and governments in 6 countries with endemically MAP-infected animals [116].…”
Section: Future Considerationsmentioning
confidence: 99%